57.5k views
2 votes
Sec squared 55 - tan squared 55

User Faulty Orc
by
5.4k points

1 Answer

7 votes

Answer:

sec squared 55 – tan squared 55 = 1

Step-by-step explanation:

Given, sec square 55 – tan squared 55

We know that,


\sec \Theta=\frac{\text {hypotenuse}}{\text {base}}

And,


\tan \theta=\frac{\text { perpendicular }}{\text { base }}

where Ө is the angle

Substituting the values


\left(\frac{\text {hypotenuse}}{\text {base}}\right)^(2)-\left(\frac{\text { perpendicular }}{\text {base}}\right)^(2)

Solving,


\frac{(\text {hypotenuse})^(2)-(\text {perpendicular})^(2)}{(\text {base}) *(\text {base})}

According to Pythagoras theorem,


\text { (hypotenuse) }^(2)-\text { (perpendicular) }^(2)=(\text { base })^(2)

Putting this in the equation;

squared 55 - tan squared 55 =


\frac{(\text {hypotenuse})^(2)-(\text {perpendicular})^(2)}{(\text {base}) *(\text {base})}=\frac{(\text {base})^(2)}{(\text {base}) *(\text {base})}=1

Therefore, sec squared 55 – tan squared 55 = 1

User Mangesh
by
5.3k points